University learning in the context ASPO (Social, Preventive and Compulsory Isolation) (Revista de Psicología, 2020)
This article presents a descriptive approach to the student experience of university learning in the context of ASPO (Preventive and Mandatory Social Isolation) due to the Covid-19 pandemic. For this, a Google form was made with questions -open and closed- that was sent via email to students of all careers of the Teresa de Ávila UCA Faculty, Paraná Headquarters during the month of June of this year. It was answered voluntarily by 152 students from careers corresponding to the Humanities Department. It presents a general description of the students who answered the questionnaire, the resources they have for the course, the use of the virtual platform EVA (Virtual Learning Environments) and the learning experience during the ASPO. The latter was categorized according to the learning of technological, bonding, self-organization and self-management resources. In addition, the difficulties they encountered are mentioned, such as changes in routines and daily life, relationships with teachers, being a newcomer, communication mediated by technology and digital skills and finally, the support they have and the demands or needs to be able to continue with the course in a remote manner.
Keywords: University learning; Preventive and compulsory social isolation; Student experience